Analisis Kebutuhan Teknologi Informasi Untuk Mendukung Layanan Griya Singgah Pasien YBM PLN Menggunakan Pendekatan ITIL 4 - Yuniar Antika Sari; Fitria Azzhara; Arsika; Fenny Purwani (Journal of Information Systems and Business Technology, 2026)
Technological advances in information systems have prompted organisations to improve the quality of their services by utilising integrated systems. Griya Singgah Pasien YBM PLN is a social facility that provides temporary accommodation for patients and their families who are undergoing treatment at referral hospitals. However, there are still some issues in the delivery of services, such as manual data recording, real-time access to room availability information, poor documentation of complaints management, and a conventional reporting process. This study aims to analyse the need for information technology to support the improvement of services at Griya Singgah Pasien YBM PLN. The research method used was descriptive qualitative through observation, interviews, and document studies. The analysis was conducted using the Information Technology Infrastructure Library (ITIL 4) approach, which focuses on the Service Request Management, Incident Management, Service Desk, Monitoring and Event Management, and Continual Improvement practices. Business Process Model and Notation (BPMN) was also used to model the existing business processes, enabling the identification of system requirements in a structured manner. The results of the study show that a web-based information system is needed to support patient registration, room management, complaint management, service monitoring, and automatic reporting. Implementasi sistem ini diharapkan dapat meningkatkan efisiensi operasional, kualitas layanan, dan kepuasan pengguna di Griya Singgah Pasien YBM PLN.